2014
DOI: 10.5005/jp-journals-10024-1584
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Evaluation of Color Changes of Bleach-shade Resin-based Composites after Staining and Bleaching

Abstract: Spectrophotometric evaluation of color changes of Bleachshade resin-based composites after staining and bleaching.Aim: The aim of this study was to evaluate the color stability of two commercially available bleach-shade resin composites (RC) after exposure to 3 storage solutions and the effect of 3 bleaching agents on the color stability and stain removal from stained RC. Materials and methods:Two bleach-shade RC were evaluated in this study, including a nanofilled RC, Filtek TM Z350 XT (FZ), and a nanohybrid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 39 publications
5
54
0
Order By: Relevance
“…Therefore, several studies have evaluated the color stability of composites subjected to staining solutions. In the most of these studies, the specimens have been immersed in coffee, grape juice, wine, and other beverages uninterruptedly for long periods of time (hours or days) . However, the exposure of composite restorations to beverages in vivo occurs through several cycles of a few seconds each.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, several studies have evaluated the color stability of composites subjected to staining solutions. In the most of these studies, the specimens have been immersed in coffee, grape juice, wine, and other beverages uninterruptedly for long periods of time (hours or days) . However, the exposure of composite restorations to beverages in vivo occurs through several cycles of a few seconds each.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar indexes between the bleached cylinders and those observed at baseline were reached only for specimens modeled with the Adper Universal. Prior studies have demonstrated the ability of bleaching agents to reduce the color and opacity of composite specimens stained by extrinsic pigment molecules . Similar to dental bleaching performed in a tooth's hard tissues, the bleaching effect is likely to be associated with pigment molecule degradation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dental bleaching procedures, both at‐home and in‐office, are effective practices to remove intrinsic and extrinsic discoloration from the dental hard tissues . The potential effect of bleaching agents on resin composites seems to depend on type and concentration of bleaching agent, as well as on the restorative material tested . Nonetheless, the literature is not conclusive about the action of different (in‐office and at‐home) bleaching agents in different resin composite opacities .…”
Section: Introductionmentioning
confidence: 99%